Analisis Faktor Yang Mempengaruhi Rekayasa Proses Bisnis dengan Pendekatan Metode Stuctural Equation Model - Clea Putri, Famelga; Herdianzah, Yan; Ahistasari, Asih; Erniyani, Erniyani (Journal of Industrial System Engineering and Management, 2025)
BPR or business process reengineering is a process to achieve radical improvements in terms of time, quality, rewards, and of course costs by simultaneously redesigning processes, organizations, and information systems. In this study, IT/technology and HR factors (human resources) are used in re-engineering public facilities assisted by expert systems to create efficiency and effectiveness and increase value. The main factor used in this study is the management system, especially for making changes to the organizational structure, improving the administration system, and Relationship Management. The model suitability test in this report uses several criteria, including Chi-Square, GFI, AGFI, and RMSEA. Although the final model obtained a high Chi-square value (13.157) with a probability of zero, because several other criteria were met with an AGFI value above 0.9 and an RMSEA value below 0.08, the model is considered suitable. Based on the model output, it is known that not all antecedent variables have a significant influence on the consequent variables. Likewise, not all hypotheses are accepted. All antecedent variables cannot explain the consequent variables because the R2 value is less than 0.5.